Pursuing Uniqueness: Unpacking the Social Identity of Young Urban Migrants through Coffee Culture - Agung Dharma Yuda Adi Ramadhan; Dien Vidia Rosa; Hery Prasetyo (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study explores the leisure activities of young urban migrants in cafés, examining coffee as both a commodity and a modern mode of consumption within the framework of the culture industry. The choice of coffee and cafés is an inherent part of the identity of young people who want articulation space for cultural tastes and preferences. Thus, coffee culture and youth identity become crucial to elaborate the utilization of time conceptualized as determined by the capitalist production system. This research uses critical phenomenology to study urban migrant youth in Surabaya. It purposively determined eight informants consisting of university students from regencies in East Java, baristas, and café owners. Using mass culture analysis from the Frankfurt school, this research found that there is a standardization of space, either claimed as new or authentic, to emphasize the difference with existing cafés. Consequently, the subjectivities of young urban migrants in coffee culture settings are constructed in pursuit of novelty, popularised as ‘FoMO’. The study argues that the differentiation of cafés between urban and non-urban areas does not provide a clear distinction. Then, consumers and those who formulate the existence of cafés are faced with the need to create uniqueness or innovate to multiply profits. Instead of enjoying leisure, young urban migrants are absorbed and actively reproduce the existence of socially and virtually organized social systems.